Harmonization of monetary and multidimensional poverty through a threshold alignment approach - Setyawan, Novi Andy Dwi; Sulistyaningrum, Eny; Arsyad, Lincolin (Universitas Muhammadiyah Yogyakarta, 2026)
Two principal methodologies for poverty measurement are extensively used internationally: the direct approach, encompassing multidimensional indicators, and the indirect approach, based on monetary metrics. However, empirical evidence has demonstrated that the simultaneous application of both methods produces substantial discrepancies in poverty identification results. This discrepancy can be attributed to the lack of a common threshold between the two approaches. The present study addresses this issue by implementing a threshold alignment method using receiver operating characteristic (ROC) analysis. This threshold alignment method also indirectly mitigates the arbitrariness in determining the indicator thresholds commonly associated with the Alkire–Foster (AF) method. Furthermore, this study aims to eliminate arbitrariness in indicator weight determination through multiple correspondence analysis (MCA), thereby reducing potential researcher subjectivity in the calculation process. This study compared four methodologies: AF, ROC, AF-MCA, and ROC-MCA. The findings indicate that the ROC-MCA method yields superior evaluation results compared to alternative methods. Therefore, these findings suggest that the ROC-MCA method more accurately identifies poor households and improves upon the multidimensional poverty measurement approach originally proposed by Alkire and Foster.